The geography of financial and business services in Poland: Stable concentration and a growing division of labour. (April 2021) - Hashimoto, Tom; Wójcik, Dariusz
This commentary documents the spatiotemporal distribution of financial and business services (FABS) production in Poland, by using location quotients for employment and gross value added. Considering the growing prominence of Warsaw in the central European and international network of financial centres, one could expect increasing spatial concentration of FABS in the country. Our findings confirm the undisputed primacy of Warsaw, but also show a dynamic development of FABS in Wrocław, Poznań, and Kraków, suggesting a growing division of labour. Overall, there is little evidence to suggest consolidation of FABS in Poland.